Nanopartículas de goma do cajueiro hidrofobicamente modificadas para liberação de fármaco - Veras Neto, José Guilherme (2020)
In order to optimize the incorporation of hydrophobic drugs in nanometric matrices for controlled release, two types of modifications were made by esterification of cashew gum (GC): the grafting of propionic anhydride in the GC producing derivatives GCP1, GCP2 and GCP3 with a degree of substitution (GS) of 0.79; 1.02 e 1.33 respectively as well as the grafting of cholesterol forming the GCC derivative with GS = 0.029. The FT-IR analysis showed characteristic bands of GC in 1150, 2900 and 3400 cm-1 in the esterified derivatives in addition to the presence of a new band in 1750 cm-1 for derivatives with propionic anhydride and a small increase in the band in 2900 cm-1 for the cholesterol derivative, being an indicative that modifications have occured. The 1H NMR spectra of GCP present new signals in 1.0 and 2.3, characteristic of -CH3 and -CH2 of the propionic groups inserted into derivatives, in addition to the signals due to GC. In the 1H NMR spectra of the cholesterol-modified derivative, new low intensity signals were observed in 1.3 and 2.3 due to cholesterol protons. TGA analyzes show that cholesterol grafting did not influence the thermal stability of GC, while the increase in GS of derivatives obtained by grafting propanoate increased termal stability. The critical aggregation concentration (CAC) for GCC derivative was determined by fluorescence and showed a value of 0.5 mg/mL. Nanoparticles of the derivatives were obtained via self-organization by dialysis process. The particle sizes range for the GCA derivative from 120-350 nm depending on the concentration and it was observed that despite the difference in the GS. Propionic anhydride derivatives (GCP) had an average size of 67 nm and potential Zeta ranging from -20 to -25 mV. The indomethacin release profiles showed that for the GCC derivative the release balance was reached in 8 hours, releasing 100% of the drug, being the non-Fickian release mechanism. For derivatives with propionic anhydride the released of indomethacin is inversely proportional to GS. In 48h, the percentage of indomethacin release for GCP1, GCP2 and GCP3 was 60, 45 and 36%, respectively. The release mechanism in propionic derivatives is Fickian.